복지관 이용 노인의 건강상태와 건강행위 관련요인 - 하지연(Ha, Ji-Yeon); 박연환(Park, Yeon-Hwan) (Sŏngin Kanho Hakhoe chi, 2015)
Purpose: The aim of this study was to describe health status and to identify the factors related to health behavior in older adults in South Korea. Methods: A cross-sectional survey was conducted with a convenience sample of 186 older people (mean age =68.2yrs, 65.1% Female) registered at one senior center. Data were collected by self-report questionnaires or through face to face interview. The instruments were the Modified Health Behavior Assessment Scale, Stanford Research Instruments for Chronic Disease, Self-Efficacy, SOF Frailty Index and Quality of life questionnaire. The data were analyzed using t-test, ANOVA, Pearson's correlation, and stepwise multiple regression. Results: 58.6% older adults perceived their health status positively. Education level and economic status were significantly related to health behaviors of older adults. Self-rated health, sleep, stress, quality of life, health distress, depression, and frailty were significantly correlated with the health behaviors of older adults. Frailty, education level, and sleep disturbance were the significant factors predicting the health behaviors. Conclusion: The findings from this study suggest that nurses should take into consideration education level of older adults to promote their health behaviors and health promotion program which focuses on maintaining the quality of sleep and preventing frailty.